From the history of research on entomology and plant protection in the Karaganda region - Abukenova, V.S. (Fundamental and Experimental Biology, 2022)
Boris Nikolayevich Mukhachev was the Dean of the Faculty of Natural Sciences of the Karaganda Pedagogical Institute from 1958 to 1963. He was an extraordinary man, inventor,agronomist-innovator obsessed with his work. At the beginning of his work in agriculture, he began to design mechanical devices to accelerate and facilitate the process of pollination of grain with agrochemicals andreceived two copyright certificates. The young innovator Mukhachev was a participant in the First All-Union Agricultural Exhibition in 1939. The historical trials that befell biologists in the USSR in the 30–40 years of the last century left a mark on his biography. He was among 200 advanced agronomists of Karlag. Mukhachev was engaged in the selection of winter crops in Kazakhstan. He led the fight against locusts and malaria in the Karaganda region. He successfully developed the experience of innovative work with agricultural plants and harmful insects in the fields of Central Kazakhstan. Mukhachev was engaged in pedagogical activity at the Karaganda Pedagogical Institute. Nevertheless, he remained a practitioner and a scientist, organizing the agrochemical laboratory and advanced training courses in the field of agricultural chemicalization for agronomists from different regions of Kazakhstan. The agrobiological station (of the Faculty of Natural Sciences of KarPI and later of the Faculty of Biology of KarSU), created under his leadership, during its 30 years of existence has played an important role in conducting methodological, scientific and educational work in the field of plant growing, zoology, physiology, botany, ornamental gardening, plant breeding, nature conservation, meteorology.